Analisa In Silico Senyawa Biji Lada Hitam (Piper nigrum L.) Terhadap Aktivitas Antioksidan - Elis Nurul Ikhlas; Lina Rahmawati Rizkuloh; Richa Mardianingrum (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Degenerative disease is a health condition of an organ or related tissue whose condition can deteriorate over time due to changes in body cells that affect organ function as a whole. The factor is due to unhealthy life changes such as lack of activity and frequent exposure to harmful substances into the body. Degenerative diseases include hypertension, diabetes, cholesterol, cancer, and death. Harmful substances or free radicals can be inhibited by antioxidants. One drug that has antioxidant activity is ascorbic acid (Vitamin C) which functions as an immune booster and is used by the public because it is effective as an antioxidant and health therapy but there are side effects in the form of gastrointestinal. The research aimed to find candidate drug ingredients from compounds contained in black pepper seeds (Piper nigrum L.) as in silico antioxidants. The methods used are molecular docking and molecular dynamics. The results showed BLH19 had better toxicity than the comparator drug and had hydrogen interactions that could be stabilized by the amino acid Gln139. The results of molecular dynamic calculations for BLH19 have an RMSD value of 1.5 Å with a ΔGTotal of -33.50 Kcal/mol. While the comparator drug has an RMSD value of 1.6 Å with ΔGTotal -3.39 Kcal/mol. The results showed that the affinity level of ascorbic acid compared to BLH19 for the 4RP9 receptor was predicted to be a candidate for a new antioxidant drug.